Property Performance Measurement - Abu Zarin, Hasmah; Bujang, Ahmad Ariffian (Fakulti Kejuruteraan & Sains Geoinformasi, Universiti Teknologi Malaysia., 1997)
In its traditional and generally accepted sense, investors are more keen on the proper management of their property investments. This is because property investment generate positive or negative returnees. This paper attempts to discuss the usefulness of the principal measures are produced. The shortcoming of the available of property performance measurement will also be considered.